Implementasi ASEAN Tourism Strategic Plan 2011-2015 dalam Kebijakan Pariwisata Indonesia di masa Pemerintahan Jokowi - Haiyyu Darman Moenir (Department of International Relations, Universitas Andalas, 2017)
Tourism is one of the important sectors in the economic development of a country. This is evidenced by the revenue contribution of state revenues generated from the tourism sector. Indonesia under the leadership of President Joko Widodo Focused on the development of maritime shaft which one of the main concern is tourism. In the context of tourism, Indonesia has a fairly high appeal at the local and international level. Southeast Asia region incorporated in ASEAN is a good market for Indonesia in attracting the attention of ASEAN people to come and travel in Indonesia. Through joint strategy in regional tourism development, Indonesia is trying to implement ASEAN tourism policy known as ASEAN Tourism Strategic Plan (2011-2015) in domestic context through Indonesian tourism policy. This paper will focus on how the implementation of the ASEAN Tourism Strategic Plan 2011-2015 in the Indonesian Tourism Policy in the Reign of President Joko Widodo. Key words: Tourism, connectivity, policy, government, ASEAN